Does wine glass size influence sales for on-site consumption? A multiple treatment reversal design. (December 2016) - Pechey, Rachel; Couturier, Dominique-Laurent; Hollands, Gareth; Mantzari, Eleni; Munafò, Marcus; Marteau, Theresa
Abstract Background Wine glass size can influence both perceptions of portion size and the amount poured, but its impact upon purchasing and consumption is unknown. This study aimed to examine the impact of wine glass size on wine sales for on-site consumption, keeping portion size constant. Methods In one establishment (with separate bar and restaurant areas) in Cambridge, England, wine glass size (Standard; Larger; Smaller) was changed over eight fortnightly periods. The bar and restaurant differ in wine sales by the glass vs. by the bottle (93 % vs. 63 % by the glass respectively). Results Daily wine volume purchased was 9.4 % (95 % CI: 1.9, 17.5) higher when sold in larger compared to standard-sized glasses. This effect seemed principally driven by sales in the bar area (bar: 14.4 % [3.3, 26.7]; restaurant: 8.2 % [−2.5, 20.1]). Findings were inconclusive as to whether sales were different with smaller vs. standard-sized glasses. Conclusions The size of glasses in which wine is sold, keeping the portion size constant, can affect consumption, with larger glasses increasing consumption. The hypothesised mechanisms for these differential effects need to be tested in a replication study. If replicated, policy implications could include considering glass size amongst alcohol licensing requirements. Trial registration ISRCTN registry:ISRCTN12018175 . Registered 12th May 2015.